Gene deletions in spinal muscular atrophy. Issue 2 (February 1996) - Rodrigues, N R; Owen, N; Talbot, K; Patel, S; Muntoni, F; Ignatius, J; Dubowitz, V; Davies, K E
Abstract : Two candidate genes (NAIP and SMN) have recently been reported for childhood onset spinal muscular atrophy (SMA). Although affected subjects show deletions of these genes, these deletions can lead to either a very mild or a severe phenotype. We have analysed a large number of clinically well defined patients, carriers, and normal controls to assess the frequency and extent of deletions encompassing both of these genes. A genotype analysis indicates that more extensive deletions are seen in the severe form of SMA than in the milder forms. In addition, 1 center dot 9% of phenotypically normal carriers are deleted for the NAIP gene; no carriers were deleted for the SMN gene. Our data suggest that deletions in both of these genes, using the currently available assays, are associated with both a severe and very mild phenotype.